2021
DOI: 10.1111/liv.15022
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide association study identifying SVEP1 variant as a predictor of response to tolvaptan for cirrhotic ascites

Abstract: Background and Aims: Tolvaptan, an orally active vasopressin V2-receptor antagonist, has been used for patients with di cult-to-treat ascites in Japan. In this study, we conducted a genome-wide association study (GWAS) in the Japanese population to identify genetic variants associated with tolvaptan's e cacy for patients with hepatic ascites. Methods: From 2014 through 2018, genomic DNA samples were obtained from 550 patients who were treated with tolvaptan. Of those, 80 cases (non-responder; increase of body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Factors identified included baseline body weight and blood urea nitrogen levels in a post hoc analysis of the Japanese tolvaptan phase 2/3 trials, 39 and blood urea nitrogen levels, serum sodium levels, and the presence of a single nucleotide polymorphism (rs2991364) of the SVEP1 gene in a genome-wide association study in 550 Japanese patients. 40 In line with Japanese guidelines, 11,12 tolvaptan nonresponders should receive intravenous spironolactone and intravenous furosemide 20 mg, plus albumin (Figure 4). Individuals without renal dysfunction should be given intravenous potassium canrenoate 100-200 mg with intravenous furosemide 20 mg, plus albumin (Figure 3).…”
Section: Treatment Of Ascites Using Tolvaptan Is Currently Possible O...mentioning
confidence: 97%
See 1 more Smart Citation
“…Factors identified included baseline body weight and blood urea nitrogen levels in a post hoc analysis of the Japanese tolvaptan phase 2/3 trials, 39 and blood urea nitrogen levels, serum sodium levels, and the presence of a single nucleotide polymorphism (rs2991364) of the SVEP1 gene in a genome-wide association study in 550 Japanese patients. 40 In line with Japanese guidelines, 11,12 tolvaptan nonresponders should receive intravenous spironolactone and intravenous furosemide 20 mg, plus albumin (Figure 4). Individuals without renal dysfunction should be given intravenous potassium canrenoate 100-200 mg with intravenous furosemide 20 mg, plus albumin (Figure 3).…”
Section: Treatment Of Ascites Using Tolvaptan Is Currently Possible O...mentioning
confidence: 97%
“…Given the potential for improvement in prognosis, studies have investigated factors predictive of tolvaptan efficacy. Factors identified included baseline body weight and blood urea nitrogen levels in a post hoc analysis of the Japanese tolvaptan phase 2/3 trials, 39 and blood urea nitrogen levels, serum sodium levels, and the presence of a single nucleotide polymorphism (rs2991364) of the SVEP1 gene in a genome‐wide association study in 550 Japanese patients 40 …”
Section: Seven Steps In the Treatment Of Cirrhotic Ascitesmentioning
confidence: 99%
“…4 As a genetic factor, the SVEP1 rs2991364 single nucleotide polymorphism has been reported to be associated with the tolvaptan response. 13 Tolvaptan increases the serum level of albumin, decreases the ammonia level, and preserves renal function after 1 year of treatment. 14 Furthermore, it is expected to improve QOL and the survival rate of cirrhosis.…”
Section: Algorithm Of Ascites Management For Liver Cirrhosis Inmentioning
confidence: 98%
“…Therefore, tolvaptan has been presumed to be more effective for cases of early stage ascites and early initiation of tolvaptan is recommended when conventional diuretics are ineffective 4 . As a genetic factor, the SVEP1 rs2991364 single nucleotide polymorphism has been reported to be associated with the tolvaptan response 13 …”
mentioning
confidence: 99%
“…Refractory ascites, one of the most serious complications in patients with cirrhosis and ascites, has a prevalence of 5-10% in 5 years (1) and a post diagnosis survival rate of 50% at 6-12 months (2,3). Most patients with decompensated cirrhosis who develop large volumes of ascitic fluid notice abdominal distention, which may markedly impair the patients' quality of life (4). Evidencebased clinical practice guidelines for liver cirrhosis have shown that diuretic resistance or poor diuretic response is an indication for large abdominal paracentesis or cell-free and concentrated ascites reinfusion therapy (CART) (5,6), with fever, high blood pressure, headache, and shaking with chills having been reported as CART-related adverse events (7).…”
mentioning
confidence: 99%